Dishonesty and Public Employment - Cruces, Guillermo Antonio (2023)
We exploit a natural experiment to study the causal link between dishonest behavior and public employment. When military conscription was mandatory in Argentina, eligibility was determined by both a lottery and a medical examination. To avoid conscription, individuals at risk of being drafted had strong incentives to cheat in their medical examination. These incentives varied with the lottery number. Exploiting this exogenous variation, we first present evidence of cheating in medical examinations. We then show that individuals with a higher probability of having cheated in health checks exhibit a higher propensity to occupy nonmeritocratic public sector jobs later in life.